Integer aperture least-squares estimation - Teunissen, Peter (Versita, 2005)
GNSS carrier phase ambiguity resolution is the key to fast and high-precision satellite positioning and navigation. It applies to a great variety of current and future models of GPS, modernized GPS and Galileo. In [Teunissen, 2003] we described the general principle of integer aperture (IA) ambiguity estimation. In the present contribution we introduce one particular IA estimator, the integer aperture least-squares (IALS) estimator. The motivation for studying this estimator stems from the known optimality of the integer least-squares estimator. It is shown how the IALS estimator extends the integer least-squares estimator and how its performance can be measured by means of its fail-rate and success-rate.